2023
DOI: 10.1002/adsc.202300131
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium‐Catalyzed Dual C−H Activation for Regioselective Triple Annulation of Enaminones: Access to Polycyclic Naphthopyran Derivatives

Abstract: Rh‐catalyzed C−H activation of arenes for oxidative annulations with alkynes stands out as a protocol for polycyclic scaffolds. This perspective drives us to disclose herein a rhodium catalyzed regioselective triple annulation of enaminones with hydroxyl‐alkynoates via double C−H functionalization for polycyclic naphtho‐pyran scaffolds. Secondary coordination of OH in alkynoate dictated the regioselectivity. Initial lactonization occurred chemoselectively on to enamine part via carbo rhodation followed by redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Based on the results presented above and previous reports, , a plausible mechanism accounting for the formation of 3aa is proposed in Scheme . Initially, C–H bond metalation occurs with 1a to furnish intermediate I .…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Based on the results presented above and previous reports, , a plausible mechanism accounting for the formation of 3aa is proposed in Scheme . Initially, C–H bond metalation occurs with 1a to furnish intermediate I .…”
mentioning
confidence: 86%
“…As an important class of synthetic intermediates, enaminones are not only easily obtainable but also highly versatile in reactivity . Very recently, their synthetic utility has been extended to CHA reactions. , In these reactions, various alkyne and alkene derivatives were used as coupling partners (CPs) to generate functionalized carbocyclic products. For example, Zhu et al reported the reactions of aryl enaminones with alkynes to afford functionalized naphthalenes (Scheme a) .…”
mentioning
confidence: 99%
“…Along this line, they developed a triple C−H annulation of enaminones with hydroxyl alkynoates, with the in situ generated fused naphthol, which could assist further C−H annulation, leading to PAHs (Scheme 46–2). [30b] …”
Section: Reactivity Exploration Via the Development Of Catalytic Systemsmentioning
confidence: 99%
“…Surprisingly, the incipient alkenyl-palladium intermediate could not be molded for successive activation of C–H bonds in spite of its availability at a reachable distance on both sides (Scheme e, Ar 1 & Ar 2 ). With our persistent interest in the combined alkyne/C–H activation, we herein reveal the tactic of annulating maleimides in succession to isoxazole formation by successfully transporting the Pd center from C-4 to the C–H bond of arene. Despite the availability of similar aryl groups at equidistance, the annulation occurred regioselectively at the C–H of Ar 1 .…”
Section: Introductionmentioning
confidence: 99%